A nova potência da cooperação: efeitos da interatividade digital na ação coletiva empreendedora - Cintra, Hermano José Marques (2016)
Free software development communities produce complex objects organizing their collective action through mechanisms of digital interactivity. Some of them reach hundreds, even thousands, of programmers, working on, sometimes, millions lines of code. Cooperation is taken to a new level. The research has collected evidence of digital interactivity practices from a broad range of free software projects. It demonstrates how transformation in the process of communication build the social bounds necessary for collective action to be organized via internet. Survey and analysis are based on a model for the understanding of digital literacy inspired by the phenomenology of Charles Pierce and in the epistemology of Elinor Ostrom’s institutional design, associated to a nature of the firm reinterpretation. Before the method’s exposé, the text presents the phenomenon being discussed (cooperation), the object being studied (free software development communities), and the universe of the research (digital culture). The first element is treated via a critical panorama of the narrative battle between cooperation and competition. The second element receives a detailed analysis, including the question of participants’ motivation, of the technical product’s qualities, of its political perspective (internal and external), of its economical nature (good and production), and of digital interactivity in itself, central theme to the present text’s thesis. For the third element, the discussion relies on progressive concentration of focus. It starts with four key concepts for digital culture identified by Lucia Santaella, the present research’s advisor – post-humanity, hybridization, liquidity, ubiquity -, follows to virtual communities, political activism online, to reach the hacker culture, free software’s birthing bed. The study of these three elements and the application of the selected methodological instruments allow for the substantiation of high level of literacy in the observed practices of digital interactivity. The institutional analysis framework was applied to free software development, detaching three different moments and formats for collective contributions: formative (new projects), extensive (new functions), and adjustment. The research was able to associate digital communication process with its expressive, affective and cooperative powers, demonstrating how many-to-many dialogues alter scale and reach, how the permanent records rebuild trust, how asynchronous interaction remodel coordination, and how more complex interaction spaces make new forms of governance possible. Many studies have been made about connected themes, many of them were cited. The present work uses the much less frequent perspective of communication theory framing the phenomenon as under the studies of technologies of intelligence. This particular angle allowed the research to conclude with the proposition of seven interactivity design principles for entrepreneurial and cooperative collective action: (1) foment digital literacy; (2) specialize interaction spaces; (3) use active moderation; (4) mirror productive functions digitally; (5) exercise full transparency; (6) explicit merit; (7) enable open and multiple initiative